Beyond the Farm in the Farm Bill: What Nutrition Professionals Need to Know About the Nutrition Title. Issue 6 (November 2017) - Ismail, Mehreen; Wilde, Parke
Abstract : Nutrition professionals focused on populations with low or no income in the United States should stay informed and participate in discussions about 2018 Farm Bill reauthorization. The Farm Bill's nutrition title authorizes programs administered by the US Department of Agriculture, including the Supplemental Nutrition Assistance Program and food distribution programs. In the most recent 2014 Farm Bill, the nutrition title accounted for 80% of the bill's forecasted spending. This article summarizes 5 issues that may be up for debate in the coming year. Decisions about program structure and funding, benefit adequacy, and benefit redemption will influence dietary intake and food security for millions of Americans with low income.